Measuring Electrostatic Fields in Both Hydrogen Bonding and non-Hydrogen Bonding Environments using Carbonyl Vibrational Probes - Fried, Stephen D. (2013)
Vibrational probes can provide a direct read-out of the local electrostatic field in complex molecular environments, such as protein binding sites and enzyme active sites. This information provides an experimental method to explore the underlying physical causes of important biomolecular processes such as binding and catalysis. However, specific chemical interactions such as hydrogen bonds can have complicated effects on vibrational probes and confound simple electrostatic interpretations of their frequency shifts. We employ vibrational Stark spectroscopy along with infrared spectroscopy of carbonyl probes in different solvent environments and in Ribonuclease S to understand the sensitivity of carbonyl frequencies to electrostatic fields, including those due to hydrogen bonds. Additionally, we carried out molecular dynamics simulations to calculate ensemble-averaged electric fields in solvents and in Ribonuclease S, and found excellent correlation between calculated fields and vibrational frequencies. These data enabled the construction of a robust field-frequency calibration curve for the C=O vibration. The present results suggest that carbonyl probes are capable of quantitatively assessing the electrostatics of hydrogen bonding, making them promising for future study of protein function.